The Effects of Visual Masking on Recognition: Similarities to the Generation Effect - Westerman, Deanne L.; Greene, Robert L. (Journal of memory and language, 1997)
Previous research has shown that stimuli that are masked during encoding are remembered better than stimuli that are unmasked (Nairne, 1988). Four experiments were conducted that demonstrate several limitations to this effect. A recognition advantage for masked items over unmasked items was not found when the stimuli were unfamiliar low-frequency words and nonwords. A recognition advantage was also not found when the encoding task discouraged a cursory reading of the unmasked items and when masking was manipulated as a between-subjects variable. These boundary conditions resemble ones found in previous studies of the generation effect.